Cutaneous, systemic features and laboratory characteristics of late- versus adult-onset systemic lupus erythematosus in 1006 Thai patients - Kumutnart Chanprapaph (2022)
Background: Age at disease onset may modulate systemic lupus erythematosus (SLE), but its relation to cutaneous/extracutaneous manifestation remains understudied. Objective: To compare the cutaneous, systemic features, laboratory characteristics, and disease severity between late- and adult-onset SLE patients Methods: Analyses of the cutaneous, systemic involvement, laboratory investigations, SLE disease activity index 2000 (SLEDAI-2K), and disease damage were performed to compare between groups. Results: Of 1006 SLE patients, 740 and 226 had adult- (15–50 years) and late-onset (>50 years), respectively. Among 782 with cutaneous lupus erythematosus (CLE), acute CLE (ACLE) and chronic CLE (CCLE) were more common in the adult- and late-onset SLE, respectively (p = 0.001). Multivariable logistic regression analysis demonstrated that male patients and skin signs, including papulosquamous subacute CLE, discoid lupus erythematosus, and lupus profundus, were associated with late-onset SLE (all p < 0.05). Late-onset SLE had lower lupus-associated autoantibodies, and systemic involvement (all p < 0.05). ACLE, CCLE, mucosal lupus, alopecia, and non-specific lupus were related to higher disease activity in adult-onset SLE (all p < 0.001). There was no difference in the damage index between the two groups. Conclusions: Late-onset SLE had a distinct disease expression with male predominance, milder disease activity, and lower systemic involvement. Cutaneous manifestations may hold prognostic values for SLE.